Pioneer cemeteries : sculpture gardens of the old west - Stott, Annette (Lincoln, Neb. : University of Nebraska Press, 2008)
As pioneers attempted to settle and civilize the "Wild West", cemeteries became important cultural centers. As repositories of art and history, these pioneer cemeteries tell the story of communities and visual culture emerging together within the developing landscape of the Old West.
Includes bibliographical references (p. [335]-345) and index.
Keywords: Sepulchral monuments -- Rocky Mountains Region -- History -- 19th century; Cemeteries -- Rocky Mountains Region -- History -- 19th century; Pioneers -- Rocky Mountains Region